Relationship between Knowledge Level and Teacher Attitude About HIV/AIDS With Stigma Against HIV/AIDS at the Lubuk Pakam District Public Middle School in 2020 - Batara Perkasa; Novita Hasiani Simanjuntak (Talenta Publisher, 2022)
Stigma is an attribute either socially or physically that highly discredits a person, thus the person has a bad identity in social interaction in society. Stigma and discrimination are the main barriers to prevention, treatment, care, and support for people with HIV / AIDS. This study aims to determine whether there is a relationship between the level of knowledge and attitudes of teachers about HIV / AIDS with the stigma against HIV / AIDS in Lubuk Pakam District Junior High School. This research was an analytic study with cross sectional design. The population in this study were the teachers of Lubuk Pakam District Junior High School, Samples were selected using a total sampling method and 80 teachers were assessed using a questionnaire to measure the level of knowledge, attitudes and stigma of the respondents. Data collection methods in this study used primary data and data were analyzed univariately and bivariately. The results showed 66.3% of respondents had a good level of knowledge about HIV / AIDS, 92.5% of respondents had a good attitude towards HIV / AIDS and 63.7% had a good stigma about PLWHA. The results of data that was analysed using chi square test found that there was no relationship between the level of knowledge with the stigma of HIV / AIDS with p value = 0.400 (p> 0.05) and the results of data which was analysed using the fisher exact test, obtained p value = 1,000 (0.05) which meaning there was no relationship between attitude and stigma against HIV / AIDS.There was no relationship between the level of knowledge and attitudes of teachers about HIV / AIDS with the stigma against HIV / AIDS in Lubuk Pakam District Junior High School.